GE_GERICHTE P/14987/2011 vom 15. April 2013 - GE Cour de justice (2013)
; FIXATION DE LA PEINE ; SURSIS À L'EXÉCUTION DE LA PEINE ; SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE ; CONCOURS D'INFRACTIONS | CP.47; CP.42.1; CP.49; CP.43.1